Diet quality is positively associated with 100% fruit juice consumption in children and adults in the United States: NHANES 2003-2006. - O'Neil, Carol E.; Nicklas, Theresa A.; Zanovec, Michael; Fulgoni, III., Victor L.; Fulgoni, Victor L 3rd (Nutrition Journal, 2011)
Background: One hundred percent fruit juice (100% FJ) has been viewed by some as a sweetened beverage with concerns about its effect on weight. Little regard has been given to the contribution of 100% FJ to diet quality.Methods: In this study data from the 2003-2006 National Health and Nutrition Examination Survey were used to examine the association of 100% FJ consumption with diet quality in participants 2-5 years of age (y) (n = 1665), 6-12 y (n = 2446), 13-18 y (n = 3139), and 19+y (n = 8861). Two 24-hour dietary recalls were used to determine usual intake using the National Cancer Institute method. Usual intake, standard errors, and regression analyses (juice independent variable and Healthy Eating Index-2005 [HEI-2005] components were dependent variables), using appropriate covariates, were determined using sample weights.Results: The percentage of participants 2-5 y, 6-12 y, 13-18 y, and 19+y that consumed 100% FJ was 71%, 57%, 45%, and 62%, respectively. Usual intake of 100% FJ (ounce [oz]/day) among the four age groups was: 5.8 ± 0.6, 2.6 ± 0.4, 3.7 ± 0.4, and 2.4 ± 0.2 for those in age groups 2-5 y, 6-12 y, 13-18 y, and 19+y, respectively. Consumption of 100% FJ was associated with higher energy intake in 6-12 y, 13-18 y, and 19+y; and higher total, saturated, and discretionary fats in 13-18 y participants. Consumption of 100% FJ was associated with higher total HEI-2005 scores in all age groups (< 0.0001). In 100% FJ consumers, total and whole fruit consumption was higher and intake of added sugars was lower in all age groups.Conclusions: Usual intake of 100% FJ consumption exceeded MyPyramid recommendations for children 2-5 y, but was associated with better diet quality in all age groups and should be encouraged in moderation as part of a healthy diet.